AKTIVITAS MASYARAKAT DAN KULINER JAJANAN PASAR KHAS SOLO SEBAGAI SUMBER IDE PENCIPTAAN DESAIN TEKSTIL - Senja Ari Nur Dewanti; Darwoto Darwoto (Universitas Mercu Buana, 2021)
The background of designing this product is to create innovation in visual textile design, especially for surface design with traditional Solo traditional food visuals (Jajan pasar) which is contained in the atmosphere where the food is located with the intention of conveying a message so that the millennial generation knows more and wants to preserve something traditional. , and it can be started from the most common thing, namely getting to know traditional food from Solo. This work will later explore the form of traditional food, especially Solo traditional snacks and the atmosphere where the food is located which will be visualized into designs on the textile surface. This work comes because of the problem of traditional food which is now being displaced by external foods such as junk food, fast food, and western food. Apart from that, the modernization style of the teenagers is arguably westernized which also affects their diet in their daily interactions. In order to support their existence and match the lifestyle of other friends. The results of this design can be concluded into a number of things: (1) exploring the visual form of digital design with the source of the idea of